Perl for system administration - Blank-Edelman, David N. (O'Reilly, 2000)
Some people plan to become administrators. The rest of us are thrust into it: we are webmasters, hobbyists, or just the default "technical people" on staff who are expected to keep things running. After some stumbling around repeating the same steps over and over again (and occasionally paying the price when we forget one), we realize that we must automate these tasks, or suffer endless frustration. Thus enters Perl. The Perl programming language is ideal for writing quick yet powerful scripts that automate many administrative tasks. It's modular, it's powerful, and it's perfect for managing systems and services on many platforms. Perl for System Administration is designed for all levels of administrators--from hobbyists to card-carrying SAGE members--sysadmins on multi-platform sites. Written for several different platforms (Unix, Windows NT, and Mac OS), it's a guide to the pockets of administration where Perl can be most useful for sites large and small, including: Filesystem management User administration with a dash of XML DNS and other network name services Database administration using DBI and ODBC Directory services and frameworks like LDAP and ADSI Using email for system administration Working with log files of all kinds Each chapter concentrates on a single administrative area, discusses the possible pitfalls, and then shows how Perl comes to the rescue. Along the way we encounter interesting Perl features and tricks, with many extended examples and complete programs. The scripts included in the book can simply be used as written or with minimal adaptation. But it's likely that readers will also get a taste of what Perl can do, and start extending those scripts for tasks that we haven't dreamed of. Perl for System Adminstration doesn't attempt to teach the Perl language, but it is an excellent introduction to the power and flexibility of Perl, and it whets the appetite to learn more. It's for anyone who needs to use Perl for system administration and needs to hit the ground running